TREATMENT OF NON-MUSCLE-INVASIVE HIGH-RISK BLADDER CANCER - S. A. Ivanov; I. N. Zaborskii; V. S. Chaikov (Вестник урологии)
The article describes modern methods of diagnosis and treatment of non-muscle-invasive bladder cancer. Possibilities and prospects of modern methods of diagnosis and treatment. The analysis of foreign literature is given.